Analisis Penerapan PSAK 16 tentang Perlakuan Akuntansi Aset Tetap pada Perusahaan di Indonesia - Nova Nur Azizah; Rahma Aulia; Selli Dwi Parwati; Endang Kartini Panggiarti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The company plays an important role for its main goal, namely the achievement of maximum profit on the investment invested. The company must be able to manage and utilize economic resources that have been invested properly, one form of company investment is in the form of assets as used to support company operations. Every company must have fixed assets, because the role of fixed assets is very large in the company. Of the various types of assets, fixed assets are one of the important assets that support the company's operations. In terms of maximizing the use of fixed assets, a correct and appropriate policy is needed in the management of the company's fixed assets. Therefore, when making decisions, the right information tools are needed about fixed assets, one of which is based on PSAK 16. This study aims to determine the application of PSAK 16 on the accounting treatment of fixed assets in companies in Indonesia. The method used in the research is descriptive qualitative with a literature review approach. The data source used is secondary data that has been analyzed and developed in order to elaborate the research topic. Based on the results of the study, it can be concluded that the recognition, measurement, and disclosure of fixed assets in companies in Indonesia have generally been in accordance with PSAK No. 16.